MENGGALI REALITAS KERUSUHAN MEI 1998 DALAM “SAPU TANGAN FANG YIN” - Dessy Wahyuni (SALINGKA, 2015)
An essay poetry is a form of poetry which exploring the long and stage of social reality, using simple language, and doing research before, indicated by using a footnote in its presentation. The Essay Poetry of “Sapu Tangan Fang Yin” by Denny J.A. is one of the essay poetries that explores a riot in May 1998. The problem of this article is how the “Sapu Tangan Fang Yin” describes the reality of the May 1998 riot. By applying  the historical approach, the depiction of the poem about the riot is obtained. Denny J.A. as the initiator of essay poetic offers five platforms about this kind of poetry;